Appropriate Slice for Microscopic of Hepar and Kidney Mice Fixed With BNF 10% - Armalina, Desy; Elen, Mircha Restiana; Labai, Nikita Ferren (University of Muhammadiyah Semarang, 2024)
Background: Histological processing encompasses the steps of acquiring fresh tissue, preserving it through fixation to maintain its natural appearance, slicing it into thin sections, placing the sections on glass slides, and subsequently staining them. This enables the observation of various histological components within the tissue using a microscope. The objective of this study was to ascertain the microscopic characteristics of heparin preparations and the kidneys of mice (Mus musculus) through fixation using a formalin buffer solution.Method: This kind of research encompasses experimental research. The study employed a purposive sample methodology in its research design. This study concludes that preparations containing images provide a representative depic-tion of the cell nucleus, cytoplasm, and exhibit consistent coloration with different cutting thicknesses. The standard thickness for cutting the mice hepatic tissue using a microtome is 5 μm.Result: This thickness yields good microscopic results overall, with 25 field views from 5 preparations. The percentage of high-quality microscopic images obtained at this thickness is 100%. The statistical analysis revealed significant differences (p<0.05) between the 2 μm and 5 μm groups, as well as between the 5 μm and 8 μm groups. There was no statistically significant difference (p>0.05) observed between the 2 μm and 8 μm groups in terms of many aspects including structural, nucleolus, cytoplasm, color uniformity, and total structure scores.Conclusion: The optimum thickness in this research was 5 μm. Additional investigation is required to examine the microscopic characteristics of tissue samples by varying the duration of staining on the samples.